Electrodiagnostic Studies in Neurologically Asymptomatic Patients with Vitamin B12 Deficiency - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2014)
Objectives: The aim of our study was to investigate the electrophysiologic parameters in neurologically asymptomatic patients with vitamin B12 deficiency, and to compare the results with the control group and also to investigate a correlation between vitamin B12 levels and the recorded parameters. Methods: Asymptomatic and untreated patients with vitamin B12 deficiency were examined by nerve conduction studies, visual evoked potentials (VEPs), medial and tibial somatosensory evoked potentials (SEPs), and motor evoked potentials (MEPs), prospectively. Patients who have any other disease that can effect nerve conduction studies, VEPs, SEPs, and MEPs were excluded. Results: Twenty-seven patients (22 women, 5 men) with a mean age of 37.65 +/- 13.08 and 21 healthy subjects were examined. The mean vitamin B12 level was 127 +/- 35.6 (N: 200-900) in the patient group and 301 +/- 67 in the control group. There was not a statistically significant difference between the patient and control groups according to nerve conduction studies, median SEP, tibial SEP, VEP, and MEP studies (p>0.05). There was no correlation between vitamin B12 levels and median SEP, tibial SEP, VEP, and MEP parameters (p>0.05). Conclusion: To our knowledge, this is the first study that has investigated neurologically asymptomatic patients with B12 deficiency by nerve conduction studies, VEPs, SEPs, and MEPs. The electrophysiological findings may be normal in asymptomatic patients with vitamin B12 deficiency if the diagnosis is made early.
Keywords: Vitamin B12 deficiency; electrodiagnostic study; SUBACUTE COMBINED DEGENERATION; PERIPHERAL NEUROPATHY; COBALAMIN DEFICIENCY; MEGALOBLASTIC-ANEMIA; SPINAL-CORD; FEATURES; MOTOR